A mapping review of the literature on UK‐focused health and social care databases. (19th November 2014) - Cooper, Chris; Rogers, Morwenna; Bethel, Alison; Briscoe, Simon; Lowe, Jenny
Abstract Background Bibliographic databases are a day‐to‐day tool of the researcher: they offer the researcher easy and organised access to knowledge, but how much is actually known about the databases on offer? The focus of this paper is UK health and social care databases. These databases are often small, specialised by topic, and provide a complementary literature to the large, international databases. There is, however, good evidence that these databases are overlooked in systematic reviews, perhaps because little is known about what they can offer. Objectives To systematically locate and map, published and unpublished literature on the key UK health and social care bibliographic databases. Methods Systematic searching and mapping. Results Two hundred and forty‐two items were identified which specifically related to the 24 of the 34 databases under review. Conclusion There is little published or unpublished literature specifically analysing the key UK health and social care databases. Since several UK databases have closed, others are at risk, and some are overlooked in reviews, better information is required to enhance our knowledge. Further research on UK health and social care databases is required. This paper suggests the need to develop the evidence base through a series of case studies on each of the databases.